The Concept of Evaluative Language in Malay Newspaper Discourse - Sarikon, Suhaini; Abdullah, Roksana Bibi (LingPoet: Journal of Linguistics and Literary Research, 2024)
This article delves into the exploration of Evaluative Language Theory within the discourse of Malay newspapers. The study draws upon two primary news sources: "Berita Harian/Minggu Singapura" (BH S'pura) and "Berita Harian/Ahad Malaysia" (BH M'sia). Specifically, the analysis focuses on comment articles related to the tragic events of the 9/11 attacks on the World Trade Centre in New York. By selecting articles with similar thematic contexts, the analysis aims to unveil the strategies employed by these news sources through the commentators' voices aimed at influencing their readership. The study employs Systemic Functional Linguistics to scrutinize Evaluative Language, encompassing Attitude, Engagement, and Graduation, within the Malay newspaper discourse. Attitude types such as effect, judgment, and appreciation, engagement modes including monogloss and heterogloss, and graduation aspects like force and focus are crucial elements examined in this research. Through this lens, the article aims to elucidate the nuances of Evaluative Language Concepts in Malay newspaper discourse, offering insights into how these linguistic elements shape reader perception and understanding.